David James Purslove Barker. 29 June 1938—27 August 2013. (7th December 2019) - Barker, Mary; Fall, Caroline H.; Osmond, Clive; Cooper, Cyrus; Fleming, Tom P.; Thornburg, Kent L.; Burton, Graham J.
Abstract : Professor David James Purslove Barker was a physician and one of the most influential medical scientists of our time. His fetal programming hypothesis (known as the Barker Hypothesis) transformed thinking about what causes chronic diseases that are the scourge of modern society: cancer, cardiovascular disease and diabetes. The Barker Hypothesis proposed that the environment of the fetus and infant determined by maternal nutrition and exposure to infection subsequently predisposes the pathologies of later life. He challenged the idea that chronic diseases result from a combination of bad genes and unhealthy adult lifestyle. The environment of the fetus and infant, he suggested, permanently set or 'programmed' the body's metabolism and growth, and thereby pathologies of old age. His initially controversial, but now widely accepted, ideas have produced an explosion of research worldwide into the complex processes of nutrition and growth during intrauterine and early post-natal life and how these cause adult diseases. His discoveries created a new field of research, developmental origins of health and disease (DOHaD), influencing global scientific thinking. David believed that 'the poorer health of people in lower socio-economic groups or living in impoverished places was linked to past and present neglect of the welfare of mothers and babies'. Tackling the epidemics of diabetes and heart disease in the Western world and in developing countries would require, he said, a shift in focus to prioritize the health and nutrition of adolescent girls, pregnant women and infants. This focus has subsequently been enshrined in global health policies and priorities.